ANALISA KEPUASAN MASYARAKAT PADA PROGRAM E-PAK LADI DI DESA CUKURGULING KECAMATAN LUMBANG - Eni Erwantiningsih; Sri Hastari; Yesi Febriyani (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The purpose of this study was to determine the level of community satisfaction with the online administration and population service program (Dispendukcapil), namely the E-Pak Ladi.di program in Pasuruan Regency by looking at the influence of service quality and communication effectiveness. Data collection was carried out by distributing questionnaires with the accidental sampling technique and a sample of 98 people was obtained using the Slovin formula. Data were analyzed using Canonical Correlation Analysis which is an analytical method used to identify and calculate the association between two pairs of variables. . The results showed that community satisfaction with the E-Pak Ladi program in Cukurgulung Village, Pasuruan Regency was dominantly influenced by the effectiveness of communication. While community satisfaction, the factor that is dominantly influenced by the effectiveness of communication is that the community understands the stages of activity or management in the E-Pak Ladi program and the community understands the importance of this program from the written media in the village hall.